2015
DOI: 10.1016/j.devcel.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Microtubule Organization Controls Axon Caliber and Transport and Determines Synaptic Structure and Stability

Abstract: SUMMARY The dimensions of axons and synaptic terminals determine cell-intrinsic properties of neurons; however, the cellular mechanisms selectively controlling establishment and maintenance of neuronal compartments remain poorly understood. Here, we show that two giant Drosophila Ankyrin2 isoforms, Ank2-L and Ank2-XL, and the MAP1B homolog Futsch form a membrane-associated microtubule-organizing complex that determines axonal diameter, supports axonal transport, and provides independent control of synaptic dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
88
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 53 publications
15
88
0
2
Order By: Relevance
“…Defects in MT post-translational modifications were previously observed when CEP120 or SPICE1 were overexpressed (Comartin et al, 2013) or depleted (Figure 5B). These observations are consistent with recent reports implicating ANK2 in MT organization (Stephan et al, 2015), and reveal ANK2 as a key component of a PxI network that controls MT organization and centriole biogenesis.…”
Section: Resultssupporting
confidence: 93%
“…Defects in MT post-translational modifications were previously observed when CEP120 or SPICE1 were overexpressed (Comartin et al, 2013) or depleted (Figure 5B). These observations are consistent with recent reports implicating ANK2 in MT organization (Stephan et al, 2015), and reveal ANK2 as a key component of a PxI network that controls MT organization and centriole biogenesis.…”
Section: Resultssupporting
confidence: 93%
“…The distinct distribution pattern of Ank2L4 in the proximal axon is clear when compared to the general membrane marker mCD8-RFP, which was used to outline the cells (Fig 6C). This ability of part of the polypeptide encoded by the L exon to concentrate in the proximal axon suggested that Drosophila giant ankyrins may well localize to the proximal axon in addition to distal axonal regions as has been reported for motor neurons [15, 21]. …”
Section: Resultsmentioning
confidence: 66%
“…The bulk of the Drosophila XL exon has a core array of 93 highly-conserved repeats encoding 76 amino acids which has been postulated to serve as a molecular spacer, although only a fraction of the array is required for Ank2 function in maintaining axon diameter [21]. Arrays of homologous repeats are not present in vertebrate AnkGs [14], and we found repeat arrays in only a subset of the long exons (S4 Table).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations